OPTIMASI MULTI PARAMETER MESIN 3D PRINTER FDM UNTUK MATERIAL THERMOPLASTIC POLYURETHANE GUNA MENGHASILKAN ERROR DIMENSI TERKECIL MENGGUNAKAN METODE 2K FACTORIAL DESIGN - Latif, Hudan Ahmad; Rosid, Ibnu Abdul; Dewi, Grita Supriyanto; Jatiningsih, Maria Gratiana Dian (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
Fused Deposition Modeling or FDM is a 3D printing technology that is commonly used in manufacturing processes based on Additive Manufacturing Technology. One of the materials that can be used on FDM machines is thermoplastic polyurethane (TPU). One measure of the quality of printed results is the machine's accuracy in producing workpieces that have the smallest possible dimensional error. So this research aims to obtain the printing parameters that have the most influence on print results and find out the optimal combination of printing process parameters on the machine to produce the smallest dimensional error for TPU material. The design of experiment method used is 2k factorial design using 4 process parameters, 2 levels and 3 responses. The parameters used are nozzle temperature, print speed, fill density, and enclosure box. The optimization results obtained an optimal combination of printing process parameters to produce the smallest dimensional error, namely nozzle temperature of 210°C, print speed of 30 mm/s, fill density of 100%, and not using an enclosure box.